The Influence of Internal Threats on the Functioning of the Organization - Michał TUZ; Marek SZELAGOWSKI; Justyna BERNIAK-WOZNY (Communications of International Proceedings, 2021)
The aim of this article is to research the preparation level of organizations against internal cyberthreats. With each passing year, cybercrimes are becoming increasingly complex and their scale is growing in both the qualitative and quantitative dimensions. Larger sums of money are being stolen, more confidential information is being obtained, and the effects of particular attacks are becoming more severe. Organizations are becoming an increasingly attractive target in the eyes of cybercriminals. They are becoming their direct goal, as well as are seen as a point of departure toward larger attacks. This makes organizations operate in a state of constant pressure, particularly when it comes to the selection and update of their tools and methodologies related to security. In the current business landscape, all organizations are potentially under threat – regardless of their size. The development of ICT technologies has led to the exceptional ease of access to information and considerably facilitated information exchange. In effect, information has become the primary economic good, itself conditioning social development, but also bringing about crucial social, economic, and cultural threats. The article presents the types of cyberattacks, new models and methodologies of operation of cybercriminals, and the results of the authors' studies pertaining to cyberthreats in 500 organizations.
Keywords: cyberthreats; internal cyberthreat; cybercrime; security.